2005
DOI: 10.1021/jf052051r
|View full text |Cite
|
Sign up to set email alerts
|

Phytate, Calcium, Iron, and Zinc Contents and Their Molar Ratios in Foods Commonly Consumed in China

Abstract: A total of 60 food samples commonly consumed in China were analyzed for phytate using the anion-exchange method and for calcium, iron, and zinc using atomic absorption spectrophotometry. The foods analyzed included those based on cereal grains and soybean. Phytate contents expressed on a wet weight basis ranged from 0 for foods made from starches to 1878 mg/100 g for dried stick-shaped soybean milk film. The calcium contents were between 2.08 mg/100 g for ground corn and 760.67 mg/100 g for diced fried soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
4
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 37 publications
9
111
4
7
Order By: Relevance
“…The same result was observed by Ma et al (2005) who reported that Fe concentration of the faba bean grains ranged from 3.0 to 11.3 mg/100 g. The Zn concentration ranged from 1.1 to 4.4 mg/100 g. After soaking, the Fe content of the faba bean was significantly lower than raw faba bean (P<0.05). After soaking, the losses of Fe contents were 28.2 and 39.8 %.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The same result was observed by Ma et al (2005) who reported that Fe concentration of the faba bean grains ranged from 3.0 to 11.3 mg/100 g. The Zn concentration ranged from 1.1 to 4.4 mg/100 g. After soaking, the Fe content of the faba bean was significantly lower than raw faba bean (P<0.05). After soaking, the losses of Fe contents were 28.2 and 39.8 %.…”
Section: Resultssupporting
confidence: 86%
“…They are relatively inexpensive compared to meat foods and they have a high carbohydrate content (50-65 %). In China, plant foods provide at least 50 % of the dietary energy and nutrients, and faba bean is one of the most important legumes (Ma et al 2005). Faba beans are a good source of dietary minerals, such as phosphorus, potassium, calcium, sulphur, zinc and iron.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining total Fe intake was assumed to be non-haem Fe. Because we had insufficient information on the phytate content in Japanese food, we used dietary composition data from other countries (32)(33)(34)(35) . Bioavailable Fe is the amount of Fe actually absorbed and utilized in the body, and is determined by several factors, including intake of phytate, Ca, vitamin C, meat, fish, tea and coffee and the individual's Fe status.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…A forma química dos minerais e fibras contidas em alimentos ou em dietas, principalmente na presença de oxalatos e fitatos, impede a absorção de ferro, zinco, cobre e cálcio. Por isso, em dietas enterais, existe a preocupação de serem adicionados substratos que não venham a impedir a biodisponibilidade de nutrientes, levando pacientes à desnutrição de minerais essencias para as funções metabólicas do organismo humano [25][26][27] . Isso pode interferir em outros minerais e provocar deficiências múltiplas nos indivíduos.…”
Section: Discussionunclassified